Early neoproterozoic gold deposits of the Alto Guaporé province, Southwestern Amazon Craton, Western Brazil - De Melo, Rodrigo Prudente; De Oliveira, Marcos Aurélio Farias [UNESP]; Goldfarb, Richard J.; Johnson, Craig A.; Marsh, Erin E.; Xavier, Roberto Perez; De Oliveira, Leandro Rocha; Morgan, Leah E. (Society of Economic Geologists, 2022)
The Alto Guaporé gold province, southwestern Amazon craton, contains gold deposits that have been mined since the beginning of the 18th century and these deposits, together, have modern-day, pre-mining gold resources of at least 1.8 Moz. The ore is associated with quartz vein systems along the southeastern part of the Aguapei belt, a ~35-km-wide and ~500-km-long, NNW-trending shear zone formed due to reactivation of a terrane-bounding suture. The Aguapei belt evolved by ca. 1150 to 1100 Ma rifting and deposition of siliciclastic sediments in an aulacogen basin, followed by deformation and low-grade metamorphism of the sedimentary sequences during 1100 to 900 Ma terrane collision along the craton margin. The deformation was characterized by a compressional regime until ca. 950 Ma and transition to a transpressional setting during the final 50 m.y. The gold deposits are hosted in a variety of structures that are second-order to the main Aguapei shear zone. The Ernesto and Pau-a-Pique deposits are located ~40 km apart and at jogs along the Aguapei belt. They are marginal to pre-ore igneous rocks, with Ernesto hosted in the basal part of the metasedimentary Fortuna Formation that overlies tonalite and Pau-a-Pique at the contact between metasedimentary rocks and diorite. Three deformational phases comprise the compressional (D1 to D2) to transpressional (D3) tectonic events. In the Pau-a-Pique deposit and the deeper level of the Ernesto deposit, the ore-bearing veins are bedding parallel and follow D2 strike-slip and reverse fault zones, respectively. However, the veins formed during D3 reactivation of the older structures by an array of oblique accommodation faults. In contrast, ores at shallower levels of Ernesto, both in discordant and bedding-parallel veins, are hosted within a ~20-m-thick rigid metaconglomerate with associated dilation due to the structural complexity as sedimentary rocks of the Aguapei Group were folded around the dome-shaped roof of the pre-ore tonalite. The ores in both deposits, as well as in many other deposits of the province, are characterized by disseminated and vein-hosted pyrite. Gold occurs mainly as inclusions in the pyrite, with other hydrothermal phases comprising muscovite, Fe-Ti oxides, and minor apatite, chalcopyrite, and galena. Fluid inclusion data, coupled with stable isotope geochemistry and geothermometry, indicate that gold precipitated from a low-salinity, CO2-rich fluid at ~300°C and ~2.5 kbar. The source for the fluid and gold was the interbedded pelites during devolatilization of the Aguapei Group sequence. The aqueous-carbonic fluid inclusions and the narrow range of d18O values of quartz (12 ± 1‰) from many auriferous veins from the central part of the province represent a regional ore-forming fluid. The broad range of δD for hydrous minerals (-116 to -55‰) reflects influx of small amounts of meteoric water into the steeply dipping shear zones during postgold exhumation. The 40Ar/39Ar geochronology from hydrothermal muscovite indicates a widespread hydrothermal event along the belt between 928 and 920 Ma. Collectively, the geological, geochronological, and geochemical data suggest that metamorphic fluids migrated laterally into and then upward along the Aguapei belt and deposited gold in lower-order structures where strain gradients existed between lithounits. The province has many characteristics of large orogenic gold provinces worldwide and represents a highly prospective and underexplored target region for early Neoproterozoic gold, a time period that generally is not well endowed in gold ores.